Radial Growth and Wood Density Reflect the Impacts and Susceptibility to Defoliation by Gypsy Moth and Climate in Radiata Pine - Camarero, Jesús Julio; Álvarez-Taboada, Flor; Hevia, Andrea; Castedo-Dorado, Fernando (Frontiers in Plant Science, 2018)
Drought stress causes a reduction in tree growth and forest productivity, which could be aggravated by climate warming and defoliation due to moth outbreaks. We investigate how European gypsy moth (Lymantria dispar dispar) outbreak and related climate conditions affected growth and wood features in host and non-host tree species in north-western Spain. There, radiata pine (Pinus radiata) plantations and chestnut (Castanea sativa) stands were defoliated by the moth larvae, whereas Maritime pine (Pinus pinaster) was not defoliated. The gypsy moth outbreak peaked in 2012 and 2013, and it was preceded by very warm spring conditions in 2011 and a dry-warm 2011-2012 winter. Using dendrochronology we compared growth responses to climate of defoliated host species (radiata pine, chestnut) with the non-host species (Maritime pine). We also analyzed wood density derived from X-ray densitometry in defoliated and non-defoliated radiata pines. We aimed to: (i) disentangle the relative effects of defoliation and climate stress on radial growth, and (ii) characterize defoliated radiata pine trees according to their wood features (ring-width, maximum and minimum density). In defoliated (>50% of leaf area removed) radiata pines, radial growth decreased on average 74% during 2012-2013. In defoliated chestnuts growth decreased 43%, whilst in non-defoliated maritime pines growth declined 25% due to very warm-dry conditions during the prior late winter. Defoliation explained most variability in growth of defoliated radiata pines whereas climate explained substantial growth variability in defoliated chestnuts. Radiata pines produced abundant latewood intra-annual density fluctuations in 2006 and 2009 in response to wet summer conditions, suggesting a high climatic responsiveness. Minimum wood density was lower in defoliated than in non-defoliated radiata pines prior to the outbreak, but increased during the outbreak. The pre-outbreak difference in minimum wood density suggests that the trees most affected by the outbreak produced tracheids with wider lumen and were more susceptible to drought stress. This study illustrates how radial growth and wood density can be used as ecological indicators to assess the susceptibility of radiata pine to defoliation by the gypsy moth, a pest with great potential for damage to commercial forestry worldwide.